Sensing behavior of atomically thin-layered MoS2 transistors - Late, Dattatray J.; Huang, Yi-Kai; Liu, Bin; Acharya, Jagaran; Shirodkar, Sharmila N.; Luo, Jiajun; Yan, Aiming; Charles, Daniel; Waghmare, Umesh V.; Dravid, Vinayak P.; Rao, C. N. R. (ACS Nano, 2013)
Most of recent research on layered chalcogenides is understandably focused on single atomic layers. However, it is unclear if single-layer units are the most ideal structures for enhanced gas solid interactions. To probe this issue further, we have prepared large-area MoS2 sheets ranging from single to multiple layers on 300 nm SiO2/Si substrates using the micromechanical exfoliation method. The thickness and layering of the sheets were identified by optical microscope, invoking recently reported specific optical color contrast, and further confirmed by AFM and Raman spectroscopy. The MoS2 transistors with different thicknesses were assessed for gas-sensing performances with exposure to NO2, NH3, and humidity in different conditions such as gate bias and light Irradiation. The results show that, compared to the single-layer counterpart, transistors of few MoS2 layers exhibit excellent sensitivity, recovery, and ability to be manipulated by gate bias and green light. Further, our ab initio DFT calculations on single-layer and bilayer MoS2 show that the charge transfer is the reason for the decrease in resistance in the presence of applied field.

Superior field emission properties of layered WS2-RGO nanocomposites - Rout, Chandra Sekhar; Joshi, Padmashree D.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Simbeck, Adam J.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (Scientific Reports, 2013)
We report here the field emission studies of a layered WS2-RGO composite at the base pressure of similar to 1 x 10(-8) mbar. The turn on field required to draw a field emission current density of 1 mu A/cm(2) is found to be 3.5, 2.3 and 2 V/mu m for WS2, RGO and the WS2-RGO composite respectively. The enhanced field emission behavior observed for the WS2-RGO nanocomposite is attributed to a high field enhancement factor of 2978, which is associated with the surface protrusions of the single-to-few layer thick sheets of the nanocomposite. The highest current density of similar to 800 mu A/cm(2) is drawn at an applied field of 4.1 V/mu m from a few layers of the WS2-RGO nanocomposite. Furthermore, first-principles density functional calculations suggest that the enhanced field emission may also be due to an overalp of the electronic structures of WS2 and RGO, where graphene-like states are dumped in the region of the WS2 fundamental gap.

Single-layer MoSe2 based NH3 gas sensor - Late, Dattatray J.; Doneux, Thomas; Bougouma, Moussa (Applied Physics Letters, 2014)
High performance chemical sensor is highly desirable to detect traces of toxic gas molecules. Two dimensional (2D) transition metal dichalcogenides (TMDC) semiconducting materials has attracted as high performance gas sensor device applications due to unique properties such as high surface to volume ratio. Here, we describe the utilization of single-layer MoSe2 as high-performance room temperature NH3 gas sensors. Our single-layer MoSe2 based gas sensor device shows comprehensible detection of NH3 gas down to 50 ppm. We also confirmed gas sensing measurement by recording the Raman spectra before and after exposing the device to NH3 gas, which subsequently shows the shift due to charger transfer and analyte gas molecule adsorption on surface of single-layer MoSe2 nanosheet. Our investigations show the potential use of single-layer and few layer thick MoSe2 and other TMDC as high-performance gas sensors. (C) 2014 AIP Publishing LLC.

Single-layer graphene doping through molecular interaction: field-effect transistor and atomic force microscopy investigations - Late, Dattatray J. (Advanced Device Materials, 2015)
The single-layer graphene has attracted considerable attention for the promising applications in new generation nanoelectronics and optoelectronics devices because of the high deal carrier mobility. Present investigations deal with the effect of chemical/molecular doping with varying the concentration of strong electron acceptor molecule such as tetracyanoethylene (TCNE) on transfer characteristics of single-layer graphene transistor. The Dirac point shift toward the positive gate voltage as a function of increasing concentration of TCNE molecules clearly indicates that the graphene is P-type doped. Our results indicate that the fermi energy level can be controlled by the amount of molecular doping in order to obtain graphene transistors with tunable Dirac points, which can be easily configured into functional nanoelectronic devices.

Spectral analysis of the emission current noise exhibited by few layer WS2 nanosheets emitter - Suryawanshi, Sachin R.; Kolhe, Pankaj S.; Rout, Chandra S.; Late, Dattatray J.; More, Mahendra A. (Ultramicroscopy, 2015)
Spectral analysis of the field emission (FE) current fluctuations has been carried out at the base pressure similar to 1 x 10(-8) mbar. The emission current stability investigated at preset value of 2 mu A is characterized by `step like fluctuation. The spectral analysis performed on a FFT (Fast Fourier Transform) analyzer revealed that the observed noise is of 1/f(alpha) type, with the value of alpha as similar to 1.05. The estimated value of alpha implies that the current fluctuations are mainly due the various processes occurring on atomic scale like adsorption, migration, and/or desorption of the residual gas species on the emitter surface. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Current fluctuations; field emission; Noise; WS2 nanosheets

Stable field emission from layered MoS2 nanosheets in high vacuum and observation of 1/f noise - Kashid, Ranjit V.; Joag, Pracheetee D.; Thripuranthaka, M.; Rout, Chandra S.; Late, Dattatray J.; More, Mahendra A. (Nanomaterials and Nanotechnology, 2015)
Field emission and current noise of hydrothermally synthesized MoS2 nanosheets are investigated in ultra-high-vacuum and industrially suited high-vacuum conditions. The study reveals that the emission turn-on field is pressure dependent. Moreover, the MoS2 nanosheets exhibit more stable field-electron emission in high-vacuum than in ultra-high-vacuum conditions. The investigations on field-emission current fluctuations show features of 1/f-type noise in ultra-high-vacuum and high-vacuum conditions, attributed to adsorption and desorption processes. The post-field-emission results indicate the MoS2 nanosheets are a robust field emitter in high-vacuum conditions.
Keywords: Electron emission; layered materials; MoS2; Noise measurement; Raman spectroscopy

Synthesis of GdB6 nanostructures using nanosecond (Nd: YAG) laser: field emission investigation - Suryawanshi, S. R.; Late, Dattatray J.; More, Mahendra A.; Singh, Anil K.; Sinha, S. (2015 28th International Vacuum Nanoelectronics Conference (IVNC), 2015)
We herein report field emission characteristics of GdB6 nanostructures grown directly on a pellet via laser processing (laser fluence similar to 6 J/cm(2)). The laser processed GdB6 pellet was characterized by X-ray diffraction, which revealed no change in phase upon laser processing. The values of the turn-on field required to draw emission current density of 1 mu A/cm(2) is found to be similar to 2.95 V/mu m, for the laser processed GdB6 emitter. Furthermore, the Fowler-Nordheim (F-N) plot exhibits non-linear behavior over the entire range of applied field and the field enhancement factor (beta) calculated from slope of the F-N plot (low field region) was found to be similar to 543. The emission current stability over a period of 3h was observed to be fairly good. The observed results demonstrate that laser processing can be efficiently used to make GdB6 nanostructure emitter having potential for practical applications.

Single SnO2 Nanowire: field emission investigations - Joshi, D.; Joag, Dilip S.; Mulla, Imtiaz S.; Late, Dattatray J. (2016 29th International Vacuum Nanoelectronics Conference (IVNC), 2016)
The present work deals with the field emission study on multiple SnO2 nanowires synthesized by simple thermal evaporation method. For the realistic analysis of the Fowler Nordheim plot of the semiconducting SnO2, field emission behavior of a single nanowire is studied. A relevant model explaining the field emission mechanism from the single SnO2 nanowire is also proposed by the authors.
Keywords: SnO2 nanowire

Situ fabrication of highly crystalline CdS decorated Bi2S3 nanowires (nano-heterostructure) for visible light photocatalyst application - Panmand, Rajendra P.; Sethi, Yogesh A.; Deokar, Rajashree S.; Late, Dattatray J.; Gholap, Haribhau M.; Baeg, Jin-Ook; Kale, Bharat B. (RSC Advances, 2016)
In situ synthesis of the orthorhombic Bi2S3 nanowires decorated with hexagonal CdS nanoparticles (nano-heterostructure) has been demonstrated by a facile solvothermal method. The tiny 5-7 nm CdS spherical nanoparticles are decorated on the surfaces of 30-40 nm Bi2S3 nanowires, successfully. Structural, morphological and optical studies clearly show the existence of CdS on the nanowires. A possible sequential deposition growth mechanism is proposed on the basis of experimental results to reveal the formation of the nano heterostructure. The heterostructures have been used as a photocatalyst for hydrogen production as well as degradation of methylene blue under solar light. The maximum hydrogen evolution i.e. 4560 and 2340 mu mol h(-1) 0.5 g was obtained from H2S splitting and glycerol degradation for Bi2S3 NWs decorated with CdS nanoparticles (nano-heterostructure) which is higher than that of the Bi2S3 NWs (3000 and 1170 mu mol h(-1) 0.5 g, respectively). The enhanced photocatalytical hydrogen evolution efficiency of the heterostructures is mainly attributed to its nanostructure. In the nano heterostructure, the CdS nanoparticles control the charge carrier transition, recombination, and separation, while the Bi2S3 nanowire serves as a support for the CdS nanoparticles. The photogenerated electron's migration is faster than the holes from the inside of a CdS nanoparticle to its surface or to the phase interface, resulting in a relatively higher hole density inside the CdS nanoparticle leaving electron density at surface of the Bi2S3 NWs. This influences the photocatalytic activity under solar light. Such nano-heterostructures may have potential in other photocatalytic reactions.

SnS2 nanoflakes for efficient humidity and alcohol sensing at room temperature - Bharatula, Lakshmi Deepika; Erande, Manisha B.; Mulla, Imtiaz S.; Rout, Chandra Sekhar; Late, Dattatray J. (RSC Advances, 2016)
We report a one step facile hydrothermal synthesis of layered SnS2 nanoflakes. The as-synthesized nanosheets are characterized using X-ray diffraction, Raman spectroscopy and Transmission Electron Microscopy (TEM). The humidity sensing behavior of SnS2 nanoflake sensor device were investigated in the range of 11-97% of relative humidity (RH) at room temperature. The response time of similar to 85 s and recovery time of similar to 6 s were observed for the SnS2 nanoflake based humidity sensor. A maximum sensitivity of 11.300% is recorded. We also investigate the SnS2 nanoflake based alcohol sensing properties towards methanol, ethanol and iso-propyl alcohol. An exclusive selectivity towards methanol with a response of 1580 is shown as compared to other analytes. The response time of similar to 67 s and recovery time of just 5 s were observed for the SnS2 nanoflake based methanol sensor.

Spatially branched CdS-Bi2S3 heteroarchitecture: single step hydrothermal synthesis approach with enhanced field emission performance and highly responsive broadband photodetection - Bankar, Prashant K.; Pawar, Mahendra S.; Pawbake, Amit S.; Warule, Sambhaji S.; Late, Dattatray J.; More, Mahendra A. (RSC Advances, 2016)
This report explores the controlled hierarchical synthesis of CdS nanostructure branches on Bi2S3 nanorod cores via a facile single step hydrothermal route. Morphological and structural studies reveal the formation of CdS-Bi2S3 heteroarchitecture with excellent stoichiometry between the constituent elements. The growth of CdS over Bi2S3 strongly depends on optimization of the reaction conditions, especially low PVP concentration. Furthermore, the as-synthesized CdS-Bi2S3 heteroarchitecture demonstrates multifunctionality in field emission and photoresponse. Interestingly, the CdS-Bi2S3 heteroarchitecture shows enhanced field emission properties such as low turn-on field (similar to 1.8 V mu m(-1) for 10 mu A cm(2)), high emission current density and better current stability in comparison to Bi2S3 and other nanostructures. The as-synthesized CdS-Bi2S3 heteroarchitecture exhibits considerable response and recovery times, similar to 207 ms and 315 ms, respectively in comparison to bare Bi2S3 nanostructures (similar to 655 ms and 678 ms). The present results demonstrate CdS-Bi2S3 heteroarchitecture as a potential candidate for future optoelectronic device applications.

Surface chemical bonds, surface-enhanced Raman scattering, and dielectric constant of SiO2 nanospheres in-situ decorated with Ag-nanoparticles by electron-irradiation - Phatangare, A. B.; Dhole, S. D.; Dahiwale, S. S.; Mathe, V. L.; Bhoraskar, S. V.; Late, Dattatray J.; Bhoraskar, V. N. (Journal of Applied Physics, 2016)
Nanostructures of dielectric materials decorated with metal nanoparticles are of great scientific interest; however, the involved synthesis methods are complicated and require multistep chemical processing, including functionalization of the dielectric surfaces. In the present work, without chemical processes, silver nanoparticles of average sizes in the range of 11 to 15 nm were in-situ synthesized and decorated on SiO2 nanospheres in a single step process by irradiating a solution (AgNO3-polyvinylpyrrolidone (PVP)-SiO2 nanospheres) with 6 MeV electrons at 1.5 x 10(15) e(-)/cm(2), 3.0 x 10(15) e(-)/cm(2), and 4.5 x 10(15) e(-)/cm(2) fluences. The electron irradiated solutions were characterized with different surface and other techniques. The results revealed that the SiO2 nanospheres were uniformly decorated with Ag nanoparticles, and the prominent chemical bonds involved were Ag-O, Si-O-Ag, and Si-Ag. Moreover, the sizes and the decoration density of Ag nanoparticles could be tailored by varying electron fluence. The Surface-enhanced Raman scattering (SERS) of 4-aminothiophenol (4-ATP) solutions was studied using substrates in the form of thin coatings of the solutions of Ag-decorated SiO2 nanospheres. The appearance of the characteristic SERS peaks of both 4-ATP and 4, 4'-dimercaptoazobenzene (4, 4'-DMAB) in Raman spectra confirmed the conversion of a fraction of 4-ATP into 4, 4'-DMAB in the presence of Ag nanoparticles. Composites in the form of thin films were synthesized from the mixture solutions of PVP and Ag-decorated SiO2 nanospheres. The dielectric constant of each thin film was higher as compared to polymers, and could be tailored by varying electron fluence used for decorating Ag nanoparticles. Published by AIP Publishing.

Surface modification of aligned CdO nanosheets and their enhanced field emission properties - Bagal, Vivekanand S.; Patil, Girish P.; Deore, Amol B.; Suryawanshi, Sachin R.; Late, Dattatray J.; More, Mahendra A.; Chavan, Padmakar G. (RSC Advances, 2016)
Porous aligned CdO nanosheets were grown on a cadmium (Cd) substrate by the simple and cost effective method of thermal annealing. Further, decoration of gold (Au) nanoparticles on the porous aligned CdO nanosheets (specimen A) was achieved by coating with a Au thin film and subsequent annealing treatment. The average diameters of decorated Au nanoparticles were found to be 15 nm, 21 nm and 28 nm for the Au thin films with 20 s, 40 s and 60 s (specimens B, C, and D) coating times. Detailed characterizations, such as structural and morphological analysis of porous CdO nanosheets and Au/CdO nanocomposite (Au decorated porous CdO nanosheets), have been carried out using a Field Emission Scanning Electron Microscope (FESEM), X-ray diffraction (XRD) and a Transmission Electron Microscope (TEM). Field emission studies of specimens A, B, C and D were carried out in the planar diode configuration. Turn-on fields of 1.9 V mu m(-1), 1.1 V mu m(-1), 2.4 V mu m(-1) and 2.8 V mu m(-1) have been found for the emission current density of 10 RA cm(-2) for specimens A, B, C and D, respectively. The observed low turn -on field of specimen B (Au diameter of 15 nm) was found to be superior to other semiconducting nanostructures reported in the literature. The field emission current stability over a period of 3 h at the preset current density of 1 RA cm(-2) is found to be excellent for all specimens. To the best of our knowledge, field emission studies along with surface modification of porous aligned CdO nanosheets have not been reported in the literature. The simple synthesis route, facile surface modification and the superior field emission results make the present emitter very suitable for micro/nano electronic devices.

Synthesis and self-assembly of dumbbell shaped ZnO sub-micron structures using low temperature chemical bath deposition technique - Borade, P.; Joshi, K. U.; Gokarna, A.; Lerondel, G.; Walke, P.; Late, Dattatray J.; Jejurikar, S. M. (Materials Chemistry and Physics, 2016)
We report well dispersed horizontal growth of ZnO sub-micron structures using simplest technique ever known i.e. chemical bath deposition (CBD). A set of samples were prepared under two different cases A) dumbbell shaped ZnO grown in CBD bath and B) tubular ZnO structures evolved from dumbbell shaped structures by dissolution mechanism. Single phase wurtzite ZnO formation is confirmed using X-ray diffraction (XRD) technique in both cases. From the morphological investigations performed using scanning electron microscopy (SEM), sample prepared under case A indicate formation of hex bit tool (HBT) shaped ZnO crystals, which observed to self-organize to form dumbbell structures. Further these microstructures are then converted into tubular structures as a fragment of post CBD process. The possible mechanism responsible for the self-assembly of HBT units to form dumbbell structures is discussed. Observed free excitonic peak located at 370 nm in photoluminescence (PL) spectra recorded at 18 K indicate that the micro/nanostructures synthesized using CBD are of high optical quality. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Electron microscopy (STEM; Microstructure; Nanostructures; Optical properties; Photoluminescence spectroscopy; Raman spectroscopy and scattering; TEM and SEM)

Synthesis of Ni-doped ZnO nanostructures by low-temperature wet chemical method and their enhanced field emission properties - Rana, Amit Kumar; Bankar, Prashant; Kumar, Yogendra; More, Mahendra A.; Late, Dattatray J.; Shirage, Parasharam M. (RSC Advances, 2016)
In this study, we report an enhancement in the field emission (FE) properties of ZnO nanostructures obtained by doping with Ni at a base pressure of similar to 1 x 10(-8) mbar, which were grown by a simple wet chemical process. The ZnO nanostructures exhibited a single-crystalline wurtzite structure up to a Ni doping level of 10%. FESEM showed a change in the morphology of the nanostructures from thick nanoneedles to nanoflakes via thin nanorods with an increase in the Ni doping level in ZnO. The turn-on field required to generate a field emission (FE) current density of 1 mu A cm(-2) was found to be 2.5, 2.3, 1.8 and 1.7 V mu mcm(-2) for ZnO (Ni0%), ZnO (Ni5%), ZnO (Ni7.5%) and ZnO (Ni10%), respectively. A maximum current density of similar to 872 mu A cm(-2) was achievable, which was generated at an applied field of 3.1 V mu m cm(-2) for a Ni doping level of 10% in ZnO. Long-term operational current stability was recorded at a preset value of 5 mA for a duration of 3 h and was found to be very high. The experimental results indicate that Ni-doped ZnO-based field emitters can open up many opportunities for their potential use as an electron source in flat panel displays, transmission electron microscopy, and the generation of X-rays. Thus, the simple low-temperature (similar to 80 degrees C) wet chemical synthesis approach and the robust nature of the ZnO nanostructure field emitter can provide prospects for the future development of cost-effective electron sources.

Synthesis of orthorhombic-molybdenum trioxide (α-MoO3) thin films by hot wire-CVD and investigations of its humidity sensing properties - Jadkar, Vijaya; Pawbake, Amit S.; Waykar,Ravindra G.; Jadhavar, Ashok Arjun; Mayabadi, Azam; Date, Abhijit; Late, Dattatray J.; Pathan, Habib M.; Gosavi, Suresh W.; Jadkar, Sandesh R. (Journal of Materials Science Materials in Electronics, 2017)
In present work, we report synthesis of orthorhombic-molybdenum trioxide (α-MoO 3) thin films using home-build hot wire-CVD (HW-CVD) method simply by heating the Mo filament in a controlled O 2 atmosphere. The formation of α-MoO 3 was confirmed by low angle-XRD and Raman spectroscopy. Low angle-XRD analysis revealed that α-MoO 3 crystallites have orientations along (110), (101) and (111) directions while Raman spectroscopy analysis shows two prominent vibrational modes ~819 and ~994 cm −1 associated with Mo 2–O and Mo=O respectively. SEM and TEM analysis show the formation of nano-sheets like morphology of α-MoO 3 thin films. The SAED pattern shows highly crystalline nature of α-MoO 3. The humidity-sensing properties were investigated at room temperature by fabricating the two probe device. The humidity sensing results showed n-type behavior of α-MoO 3. The maximum humidity sensitivity of ~6957% along with response time of ~66 s and recovery time of ~5 s were observed for α-MoO 3 thin film humidity sensor device. Our results have opened up a new avenue to grow α-MoO 3 for humidity sensor applications.

Superior humidity sensor and photodetector of mesoporous ZnO nanosheets at room temperature - Gupta, Shobhnath P.; Pawbake, Amit S.; Sathe, Bhaskar R.; Late, Dattatray J.; Walke, Pravin S. (Sensors and Actuators B-Chemical, 2019)
Miniaturized sensor technology is vastly demanding multifunctional materials to fulfill many requirements simultaneously; instead of integrating various sensors into a single device. Efficient operation of these miniaturized sensors at room temperature is highly feasible and cost-effective. The humidity sensing and photodetection is precise merit of sensing in special usage like artificial skin. Sensitivity enhancement in both humidity and photodetection required the high surface area for adsorption as well as a high charge transfer mechanism. The two dimensional (2D) zinc oxide nanosheets (ZnO NS) is the ultimate structure for dimensionally confined transport properties owing to the specific surface atomic configuration that results in high sensitivity, low operating temperature, fast response and recovery, and improved selectivity. Furthermore, introducing porosity into 2D nanostructures has opened new opportunities to enhance the efficiency of sensors and detectors via increasing large surface area and tunable physical and chemical properties. Here we report preparation of mesoporous and highly crystalline 2D ZnO NS by a single step, template free, cost-effective chemical method. The structural and morphological characterizations of ZnO NS are carried out using XRD, FESEM, XPS, TEM respectively. The high-resolution TEM images emphasize sheet-like morphology with a thickness of around 18-22 nm. Further the mesoporous ZnO NS (MZNS) with the pore size between 5-10 nm are achieved by simple heat-treatment. XPS and PL study is confirming the oxygen deficiency in MZNS. The MZNS exhibits an excellent responsivity than PZNS with a fast response and rapid recovery time of 25 s and 5 s respectively along with good cyclic stability which is highly crucial for smart humidity sensor. Furthermore, it considerably enhances photo-sensor performance than pristine ZnO NS (PZNS) with (similar to)1 s response time as well as (similar to)1 s recovery time along with better stability. These promising results illustrate the great potential of MZNS for next-generation humidity sensors and photodetectors.
Keywords: humidity sensor; Mesoporous; nanosheets; Photo-detector

Synthesis of a 3D free standing crystalline NiSex matrix for electrochemical energy storage applications - Dinara, Syed Mukulika; Samantara, Aneeya K.; Das, Jiban K.; Behera, J. N.; Nayak, Saroj K.; Late, Dattatray J.; Rout, Chandra Sekhar (Dalton Transactions, 2019)
The electrochemical performance for energy storage of three-dimensional (3D) self-supported heterogeneous NiSex cubic-orthorhombic nanocrystals grown by a facile one-step chemical vapour deposition (CVD) approach on Ni foam substrates has been explored. NiSex shows a high specific capacitance of 1333 F g(-1) with ultra-high energy (105 W h kg(-1)) and power (54 kW kg(-1)) densities. Furthermore, by integrating the as-grown NiSex as the anode and reduced graphene oxide as the cathode, a hybrid super-capacitor (HSC) prototype with a coin cell configuration has been fabricated. The device shows better capacitance (40 F g(-1)) with high energy (22 W h kg(-1)) and power (5.8 kW kg(-1)) densities and robust cycling durability (similar to 88% capacitance retention after 10 000 repeated cycles). For practical reliability of the as-fabricated HSC, a red LED has been illuminated by connecting it with two charged coin cells. These outstanding performances of the HSC prove to be promising for applications in high energy storage systems.

Spectroscopic probe of atomically thin domains of CVD-grown MoSe2 - Singh, Vineeta; Late, Dattatray J.; Rath, Shyama (AIP Conference Proceedings, 2020)
Since the discovery of graphene, two-dimensional Layered Transition Metal Dichalcogenides (TMDCs) such as MoS2, MoSe2, and WS2 having a tunable bandgap, have emerged as one of the most stable classes of materials making them attractive for various applications. We have investigated the growth mechanism and shape evolution of various domains of CVD-grown MoSe2 on insulating substrates by spectroscopic techniques. The different morphologies were analyzed using Raman and photoluminescence spectroscopies. The transformation from the precursor MoO3 to MoSe2 is found to depend on a number of growth parameters and experimental conditions.

Size does matter: antibacterial activities and cytotoxic evaluation of polymorphic CuO nanostructures - Desai, Dnyanada G.; Navale, Govinda R.; Late, Dattatray J.; Dharne, Mahesh S.; Walke, Pravin S. (Journal of Materials Science, 2023)
Nanostructured materials play a significant role in antibacterial activities. However, understanding the geometrical influence at the nanoscale in terms of size- and shape-correlated physical properties on antibacterial activities is very essential. Herein, we report the antibacterial influence of various copper oxide nanostructures (CuO NS) such as nanoparticles (NPs) (< 10 nm), nanospheres (NSs) (50-100 nm), and porous nanoflowers (NFs) (asymptotic to 350 nm). The XRD confirmed the crystalline nature of CuO NPs without impurities. The antibacterial activities of CuO NPs were investigated by the microplate dilution method and confocal laser scanning microscopic (CLSM) imaging. NPs having a diameter less than 10 nm exhibited significant damage to the bacterial cell membrane than NSs and NFs. Interestingly, NPs illustrated relatively low antibacterial activity against Gram-negative bacteria (Pseudomonas aeruginosa and Acinetobacter baumannii) than Gram-positive bacteria (Staphylococcus aureus and Staphylococcus epidermidis). Acinetobacter baumannii was found to be more susceptible to the NPs than other bacterial strains, attributed to its increased membrane permeability. The death phase was observed at a concentration of 15.6 mu g mL(-1) and 3.9 mu g mL(-1) for P. aeruginosa and A. baumannii, respectively, when treated with CuO NP after the 8 h of incubation. Similarly, for S. aureus and S. epidermidis, the death phase was observed at the concentration of 31.2 mu g mL(-1) and 250 mu g mL(-1), respectively. Furthermore, as the cell cytotoxicity measurements against human fibroblast L9239 cells revealed that CuO NPs were safe. The morphological and cell viability assay demonstrated 100% cell survival, when treated with NPs and NSs (5, 10, and 25 mu g mL(-1)), signifies no cytotoxicity. Therefore, CuO nanoparticles can be used for clinical and therapeutic applications.